“Ali”, de María Fernanda Ampuero: una radiografía social en dos historias - Palacios, Belinda (2024)
In recent years, the short stories of Ecuadorian writer María Fernanda Ampuero have garnered increasing attention from readers, as well as from a specialized audience interested in studying her work. This brief essay aims to enrich the discussion by proposing an analysis of the short story "Ali," published in Pelea de gallos (2018). We examine the main narratological elements of the story to demonstrate how, by presenting two simultaneous stories within the same family, the author provides a fierce critique of Guayaquil society, highlighting its flaws: hypocrisy, racism, classism, and an oppressive and perverse patriarchy that permeates all social classes.